Deficiency of Complement C3a and C5a Receptors Prevents Angiotensin II–Induced Hypertension via Regulatory T Cells. Issue 7 (30th March 2018) - Chen, Xiao-Hui; Ruan, Cheng-Chao; Ge, Qian; Ma, Yu; Xu, Jian-Zhong; Zhang, Ze-Bei; Lin, Jing-Rong; Chen, Dong-Rui; Zhu, Ding-Liang; Gao, Ping-Jin
Abstract : Rationale: : Inflammation and immunity play crucial roles in the development of hypertension. Complement activation-mediated innate immune response is involved in the regulation of hypertension and target-organ damage. However, whether complement-mediated T-cell functions could regulate blood pressure elevation in hypertension is still unclear. Objective: : We aim to determine whether C3aR (complement component 3a receptor) and C5aR (complement component 5a receptor) could regulate blood pressure via modulating regulatory T cells (Tregs). Methods and Results: : We showed that angiotensin II (Ang II)-induced hypertension resulted in an elevated expression of C3aR and C5aR in Foxp3 (forkhead box P3)+ Tregs. By using C3aR and C5aR DKO (double knockout) mice, we showed that C3aR and C5aR deficiency together strikingly decreased both systolic and diastolic blood pressure in response to Ang II compared with WT (wild type), single C3aR-deficient (C3aR−/−), or C5aR-deficient (C5aR−/−) mice. Flow cytometric analysis showed that Ang II-induced Treg reduction in the kidney and blood was also blocked in DKO mice. Histological analysis indicated that renal and vascular structure remodeling and damage after Ang II treatment were attenuated in DKO mice compared with WT mice. In vitro, Ang II was able to stimulate C3aR and C5aR expression in cultured CD4+CD25+ natural Tregs. CD3 and CD28 antibody stimuli downregulated Foxp3 expression in WT but not DKO Tregs. More important, depletion of Tregs with CD25 antibody abolished the protective effects against Ang II-induced hypertension and target-organ damage in DKO mice. Adoptive transfer of DKO Tregs showed much more profound protective effects against Ang II-induced hypertension than WT Treg transfer. Furthermore, we demonstrated that C5aR expression in Foxp3+ Tregs was higher in hypertensive patients compared with normotensive individuals. Conclusions: : C3aR and C5aR DKO-mediated Treg function prevents Ang II-induced hypertension and target-organ damage. Targeting C3aR and C5aR in Tregs specifically may be an alternative novel approach for hypertension treatment. Abstract : Supplemental Digital Content is available in the text.